2004
DOI: 10.1016/j.femsle.2004.01.045
|View full text |Cite
|
Sign up to set email alerts
|

PknH, a transmembrane Hank's type serine/threonine kinase fromMycobacterium tuberculosisis differentially expressed under stress conditions

Abstract: Serine/threonine protein kinases (STPKs) represent a burgeoning concept in prokaryotic signaling and have been implicated in a range of control mechanisms. This paper describes the enzymatic and molecular characterization of PknH, a mycobacterial STPK. After cloning and expression as a Glutathione-S-transferase fusion protein in E. coli, PknH was found to phosphorylate itself and exogenous substrates like myelin basic protein and histone. The kinase activity of PknH was inhibited by the kinase inhibitors staur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…GarA contains a forkhead-associated domain known to bind phosphopeptides and has previously been reported as a PknB and PknG substrate (19). As PknF and PknH displayed reduced activity on GarA, we confirmed that these two STPKs were active on myelin basic protein (MyBP), a model substrate previously reported to be phosphorylated by these kinases (44,45). PknF and PknH display equal trans-phosphorylation activity on MyBP in comparison with PknB when imaged by Pro-Q Diamond phosphoprotein gel stain (Invitrogen) (Fig.…”
Section: Stpk Intermolecular Phosphorylation Follows Specificsupporting
confidence: 82%
See 1 more Smart Citation
“…GarA contains a forkhead-associated domain known to bind phosphopeptides and has previously been reported as a PknB and PknG substrate (19). As PknF and PknH displayed reduced activity on GarA, we confirmed that these two STPKs were active on myelin basic protein (MyBP), a model substrate previously reported to be phosphorylated by these kinases (44,45). PknF and PknH display equal trans-phosphorylation activity on MyBP in comparison with PknB when imaged by Pro-Q Diamond phosphoprotein gel stain (Invitrogen) (Fig.…”
Section: Stpk Intermolecular Phosphorylation Follows Specificsupporting
confidence: 82%
“…STPK Expression and Purification-Proteins were expressed in Escherichia coli BL21 CodonPlus (Agilent) cells using autoinduction (44). Cultures were grown at 37°C for 8 h and shifted to 18 -22°C for 18 -24 h. Following harvest by centrifugation and storage at Ϫ80°C, each pellet was resuspended in 300 mM NaCl, 25 mM HEPES, pH 8.0, 25 mM imidazole, 0.5 mM tris(2-carboxyethyl)phosphine, and 10% (v/v) glycerol with 250 M 4-(2-aminoethyl)benzenesulfonyl fluoride and lysed using sonication.…”
Section: Methodsmentioning
confidence: 99%
“…It remains to be determined whether PknF directly regulates glucose transport, possibly through regulation of the ABC transporter Rv1747, and how this is able to affect cellular growth and septation. PknH phosphorylates the OmpR-like EmbR transcription factor thought to be involved in regulating genes coding for arabinosyl transferases (285,372). Instead of regulating bacterial proteins, PknG modulates the response by macrophages to infection with M. tuberculosis (80,431).…”
Section: What Are Stpks and How Do They Work?mentioning
confidence: 99%
“…In bacteria, signal transduction events are mediated by two-component regulatory systems (23,53) and protein kinases and phosphatases (5,14,48). M. tuberculosis possesses 11 protein serine/threonine kinases (3,12), of which 8 members of the kinases, including PknH kinase, have been shown to possess the catalytic enzyme activity in vitro (4,8,13,22,26,32,33,47). Except in the case of PknF and PknH, the identities of the intracellular target proteins of protein serine/threonine kinases of M. tuberculosis are yet to be identified (33,34).…”
mentioning
confidence: 99%